Perlindungan Hukum Terhadap Justice Collaborator Dalam Hukum Pidana di Indonesia : Analisis Putusan Mahkamah Agung No. 2223K/Pid.Sus/2012 - Muhammad Iqbal Lubis; Syafruddin Kalo; Madiasa Ablisar; Muhammad Hamdan (Universitas Sumatera Utara, 2019)
Abstract.Corruption is detrimental to the country's socio-economic and financial community. Criminal acts of corruption had a tendency of done more than one person. Criminal acts of corruption that has been caught by the corruption eradication Commission (KPK) has the constraint to uncover and arrest those who have committed criminal acts of corruption due to lack of information or data. Then munculah the idea of Justice Collaborator (JC) who first became known in America in 1970-an idea that is working to reveal the masterminds of major criminal acts of corruption with the convicted person criminal acts of corruption. A key role that belongs to the justice collaborator among others to uncover a criminal act or an impending criminal acts, so the return on assets from the proceeds of a criminal act can be achieved to the State. Research methods used in this research is descriptive analytic in nature, i.e. the data analysis used in the legal materials in the study will be conducted in a qualitative and comprehensive analytical data primary and secondary, this type of research is the normative legal research, collection of data used in this research is to include research libraries (Library Research). In addition to complete secondary data, primary data is also supported. Presence of Justice Collaborator in the process of investigation, investigators and Investigators by itself can be helped in uncovering the facts and find the material that originally covered became ablaze. The existence of the White Blower and Justice Collaborator in this step is helping police in the search for and find the facts related to the crime before the evil done and after crimes were committed. Countries through the Agency of protection of witnesses and victims (LPSK) is obligated to provide protection if needed. According to the above law the so-called protection is all the efforts the fulfillment of rights and the granting of aid to provide a sense of security to the witnesses or the victim must be carried out by the LPSK or any other institution. Application of Justice Collaborator has been set at SEMA No. 4 Year 2011 about Treatment For Reporting Crime (Whistle-blowers) and witnesses the Perpetrators Cooperate (Justice Collaborators) in Matters criminal acts of corruption. The defendant here because it has helped the party investigation got remission of prison for 28 months. This form of remission awards because thanks to the accused parties of investigation get other suspects to the detriment of the nation. Keywords: legal protection, justice collaborator, criminal law